Comparison of the Effectiveness of Two Different Extracorporeal Shock Wave Therapy Regimens in the Treatment of Patients With Myofascial Pain Syndrome - Ali GÜR,; İrfan KOCA,; Hilal KARAGÜLLÜ,; Özlem ALTINDAĞ,; Ercan MADENCİ,; Ahmet TUTOĞLU,; Ahmet BOYACI,; Mustafa IŞIK4, (Archives of Rheumatology, 2014)
Objectives: This study aims to compare the effectiveness of two different regimens of extracorporeal shock wave therapy (ESWT) in the treatment of myofascial pain syndrome. Patients and methods: Sixty four patients with active myofascial trigger points in the trapezius muscle were included in this study. Patients were randomized into two groups as patients undergoing a single session of low-energy [energy flux density (ED=0.25 mJ/mm2)] ESWT (group 1) and patients undergoing three sessions of ESWT with the same energy density, with one-week intervals (group 2). The effectiveness of therapy was evaluated using the number of trigger points, the Patient Global Assessment and Physician Global Assessment scales, the Neck Pain and Disability Scale, the Nottingham Health Profile and the Hamilton Anxiety Rating Scale prior to therapy and at the end of three and 12 weeks. Results: No serious complication associated with ESWT application was observed. At the end of the treatment, statistically significant improvements were achieved in the number of trigger points, pain, quality of life, and anxiety scores of patients in both groups (p<0.01). When the groups were compared regarding the effectiveness of the treatment, the improvements in the group receiving three sessions of ESWT were higher except for the anxiety scores (p<0.05). Conclusion: Low-energy ESWT is a safe and well-tolerated therapy for patients with myofascial pain syndrome and can be more efficient when administered as a three-session treatment regimen.